Penggunaan Bahasa/Variasi Bahasa Pedagang: Diksi dan Interferensi di Pasar Cekkeng Kasuara Lama Bulukumba - Rahman, Juliana; Nirwana, Nirwana (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2025)
This research originated from the phenomenon of Language Variation between sellers and buyers in Cekkeng Traditional Market, Kasuara Lama Bulukumba Regency. The purpose of this research is to find out the diction and interference that occurs between sellers and buyers in Cekkeng Traditional Market, Kasuara Lama, Bulukumba Regency. The type of research used is descriptive qualitative approach. The data collection techniques used were free listening technique, note-taking technique and recording technique. Data analysis by means of data transcription, data collection and data description. Based on the results of the study, it was found that 1) using colloquial language that is easily understood by others and using code mix between Bugis language and Indonesian language, as well as between Makassar language dialect turatea with Indonesian language. 2) using persuasive language, 3) using family language or greetings that show social status and using greetings that show caste. While Interference, the interference found in this study is 1) phonological interference and morphological interference. Diction is the selection of words used in a communication, both oral and written. The selection of appropriate diction is due to the following reasons: 1) Maintain Message Clarity, 2) Improving Language Style, 3) Creating Emotional Effects, 4) Strengthening Communication Objectives, 5) Adjusting to the Audience. The use of language variations by traders or sellers can